Non-biopsy Strategy for the Diagnosis of Celiac Disease in Adults: A Narrative Review - Wieser, Herbert; Soldaini, Carlo; Ciacci, Carolina (Turkish Journal of Gastroenterology, 2024)
Abstract: Celiac disease (CeD) diagnosis is a complicated process, requiring a multi-step procedure and a high level of clinical knowledge. Some scientific societies, mainly from Europe and North America, have proposed appropriate guidelines for the diagnosis and management of CeD. Since duodenal biopsy is particularly challenging for children, guidelines of the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition, presented in 2012 and updated in 2020, have made it possible to avoid the biopsy in symptomatic pediatric patients with high levels of IgA anti-transglutaminase. Several parallel, similar studies in adults support the non-biopsy strategy. However, several pros and cons exist in applying such a strategy. The present narrative review reports the current evidence and the implication of omitting biopsy in the diagnosis of CeD in adults. Cite this article as: Wieser H, Soldaini C, Ciacci C. Non-biopsy strategy for the diagnosis of celiac disease in adults: A narrative review. Turk J Gastroenterol. 2024;35(8):589-598.